Numerical study of enhanced nanofluid heat transfer in an open cavity with heated obstacles using LBM - Makaoui Abdelilah; Lahmer El Bachir; Benhamou Jaouad; Moussaoui Mohammed Amine; Mezrhab Ahmed (E3S Web of Conferences)
This paper employs the lattice Boltzmann method to investigate the heat transfer properties of a nanofluid circulating within an open square cavity that contains three heated obstacles. The nanofluid is introduced into the system via a lower inlet and exits the system via an outlet located at the top of the opposite wall, flowing along the cavity walls. The study examines the effects of Reynolds number, nanoparticle size fraction and the orientation of the obstacles on both temperature distribution and the Nusselt number. The results indicate that the horizontal configuration of the barriers markedly enhances heat transfer in comparison to the vertical configuration. Furthermore, an increase in the volume fraction of nanoparticles results in enhanced heat transfer, with improvements of 16.5% for the vertical configuration and 17.5% for the horizontal configuration at a nanoparticle concentration of 5%. It is noteworthy that there is a considerable increase of approximately 152.4% in the Nusselt number when the Reynolds number is increased from 100 to 500. This study highlights the pivotal role of nanoparticle concentration and obstacle orientation in optimising the thermal management of microfluidic devices and electronic cooling systems.